Viral Disease and Lipid Peroxidation in Conditions of Biotic and Abiotic Stress of Sambucus nigra L. Plants
For the first time in Ukraine, a virus disease of elderberry (Sambucus nigra L.) was found. Plants with symptoms of a viral infection were found in 2015–2016 in the Poltava region, in 2016 the same symptoms on elder plants were disfigured in the Kiev region. The symptoms of the disease and the morphological properties of the virus were studied. We found plants with chlorotic symptoms, mosaic and chain mail, plants rolling on the tops of leaves, and twisting the edges. In the leaves of infected plants, filamentous virions with a particle length of 650